Trace metal distribution, assessment and enrichment in the surface sediments of Sundarban mangrove ecosystem in India and Bangladesh. (February 2018) - Ranjan, Prabhat; Ramanathan, A.L.; Kumar, Alok; Singhal, R.K.; Datta, Dilip; Venkatesh, M.
Abstract: Comparative study of trace metals distribution in the surface sediment of Sundarban mangrove ecosystem in India and Bangladesh is one of the primary baseline study done so far. Trace metal distribution assessment covering lower salinity zone to higher salinity zone was done along Matla River (tidal river) in Indian side and freshwater zone to higher salinity zone along Passur River in Bangladesh side of Sundarban; representing anthropogenic influenced area, agricultural area, tourist site and pristine area. Trace metals distribution in the surface sediments of Sundarban mangrove ecosystem shows relatively higher value of trace metals, Co, Cr, Cu, Fe, Ni, Pb and Zn in Indian part when compared to Bangladesh. Enrichment factor shows the highest enrichment of Pb in both parts of Sundarban mangroves. Co, Cr, Cu, Pb and Zn show EF > 1 indicates sediment contamination from anthropogenic activities. Cr, Ni and Pb were found to have moderate accumulation in geoaccumulation index with Fe showing high accumulation. Normalized data of trace metals shows 87.5% from Indian site and 80% of Bangladesh site as outlier, indicating anthropogenic influence. Out of total sampling site 50% of Indian and 40% of Bangladesh site show trace metal values enriched more than predicted value of trace metals indicating Indian part have more polluted sites than Bangladesh side of Sundarban, which is also confirmed by enrichment factor, I-geo and normalization values in both the sides. Highlights: Indian Sundarban mangrove shows relatively high trace metal, Co, Cr, Cu, Fe, Ni, Pb and Zn than Bangladesh part. Enrichment factor for Co, Cr, Cu, Pb and Zn; suggest contamination by anthropogenic activities in both parts of Sundarban. Cr, Ni and Pb were found to have moderate accumulation in geoaccumulation index with Fe showing high accumulation. Normalization value shows 50% of Indian and 40% of Bangladesh site as polluted. EF, I-geo and Normalization value suggests Indian part is relatively high enriched with trace metal than Bangladesh part.